Investigating the Brand Image of Dietary Supplement Brands: a case for Health-conscious South Africans - Lofthouse, Nicholas James (The IIE, 2021)
With the escalating continual purchasing and consumption of dietary supplements (DS) widening the possibility for false and misleading advertising, properly informing consumers about the supplements they are ingesting becomes even more paramount for ensuring a positive brand image. It is known that there are grey areas with regards to health claims and advertising regulations pertaining to DS’s in South Africa, as previous research indicates and confirms. DS advertising ethics in South Africa have been put in bad light previously but no attempts at reaching a health-conscious consumer centric approach for advertising supplements has been made. Global rises in health-consciousness is further exposing misleading DS advertising and health claims. Four prominent DS brands were selected for the research whereby their nutritional contents were disseminated, their advertising and health claims intricately examined and analysed in conjunction with the South African Health Products Regulatory Authority’s (SAHPRA) regulations on such health claims. The research reveals that some DS brands are misleading consumers through false health claims when their supplements contain trace elements harmful to humans. The research further uncovers a more promising way for DS brands to advertise their products; through empowering consumers through educating them to make informed decisions when it comes to their health, more specifically, to nutrition and nutritional supplementation. This report serves to encourage further research and analysis of the realm of DS’s and the advertising of, as the current body of credible literature is lacking and the need for more information is growing. This research stands to prove that there is a better, more health-conscious way forward for DS brands which aligns with a positive and health-orientated brand image safe from harmful future scrutiny to the industry. Key words: Dietary supplements, supplements, brand image, nutritional value, healthconscious, South Africa, SAHPRA and advertising. 3 I hereby declare that the Research Report submitted for the Honours in Strategic Brand Communication degree to The Independent Institute of Education is my own work and has not previously been submitted to another University or Higher Education Institution for degree purposes.
Keywords: Advertising; Health claims; Brand reputation; South Africa; Nutritional value; South African Health Products Regulatory Authority (SAHPRA); False advertising